PENGARUH SET KESEMPATAN INVESTASI, ARUS KAS BEBAS, KEPEMILIKAN INSTITUSIONAL, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Harwanto, Salsabila Fadhilah Farah; Imronudin, Imronudin (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the effect of investment opportunity set, free cash flow, institutional ownership, and capital structure on firm value. The research method used is associative quantitative with purposive sampling data collection techniques. The population of this study is the JII70 indexed companies between 2020-2022. After curating, there were 35 companies that met the criteria with a total of 105 samples. The analysis tool used is Eviews. The results showed that the investment opportunity set had no significant effect on firm value, while free cash flow, institutional ownership, and capital structure had a positive and significant effect on firm value